XXVIII. Symposium Electromagnetic Phenomena in Nonlinear Circuits (EPNC 2024): Conference Proceedings - Loukrezis, Dimitrios; Graeser, Matthias (University of Maribor Press, 2025)
The Symposium on Electromagnetic Phenomena in Nonlinear Circuits (EPNC 2024) is one of the longest-running conference series, having been established in the 1970s. The aim of Symposium is to present the recent advances in the analysis, synthesis, optimisation, and inverse problems in nonlinear electromagnetics. Over the decades, it has significantly influenced research in the field of nonlinear electromagnetics. The symposium has provided a vital platform for researchers and practitioners to exchange ideas, present groundbreaking work, and discuss the latest trends and challenges in the application of nonlinear phenomena in electrical engineering. The contributions from the 2024 EPNC are featured in these proceedings. The publications primarily focus on electrical machines, magnetic materials, bioelectromagnetics, related calculation and analysis methods.